2019
DOI: 10.1016/j.jprot.2018.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Defining the pathogenic threat of envenoming by South African shield-nosed and coral snakes (genus Aspidelaps), and revealing the likely efficacy of available antivenom

Abstract: Defining the pathogenic threat of envenoming by south african shield-nosed and coral snakes (genus aspidelaps), and revealing the likely efficacy of available antivenom. Jprot (2018), 1 Defining the pathogenic threat of envenoming by south african shield-nosed and coral snakes (genus aspidelaps), and revealing the likely efficacy of available antivenom ABSTRACT While envenoming by the southern African shield-nosed or coral snakes (genus Aspidelaps) has caused fatalities, bites are uncommon. Consequently, this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 52 publications
0
32
0
Order By: Relevance
“…Consequently, venom toxicity/pathology analyses in combination with venom proteomics, antivenomics, and/or immunological analyses have been integrated to investigate the paraspecificity of antivenoms (Calvete et al, 2009;Madrigal et al, 2012;Pla et al, 2013;Tan et al, 2015). Such studies have revealed surprising cross-reactivity of antivenoms against distinct, non-targeted, snake species, such as: (i) the potential utility of Asian antivenoms developed against terrestrial elapid snakes at neutralizing the venom toxicity of potent sea snake venoms (Tan et al, 2015), (ii) the seeming utility of African polyvalent antivenom at neutralizing the venom of a genus of elapid snakes not including in the immunizing mixture (Whiteley et al, 2019), and (iii) the potential for saw-scaled viper antivenom to be used as an alternative treatment for bites by the boomslang (Dispholidus typus) in regions where the appropriate speciesspecific antivenom is unavailable or unaffordable (Ainsworth et al, 2018). The later of these studies demonstrated crossneutralization between distinct snake lineages (e.g., viper and colubrid), and this surprising finding was ultimately informed by venom comparisons indicating that these snakes had converged upon similar toxin compositions.…”
Section: Therapeutic Implications Treating Snake Envenomationmentioning
confidence: 99%
“…Consequently, venom toxicity/pathology analyses in combination with venom proteomics, antivenomics, and/or immunological analyses have been integrated to investigate the paraspecificity of antivenoms (Calvete et al, 2009;Madrigal et al, 2012;Pla et al, 2013;Tan et al, 2015). Such studies have revealed surprising cross-reactivity of antivenoms against distinct, non-targeted, snake species, such as: (i) the potential utility of Asian antivenoms developed against terrestrial elapid snakes at neutralizing the venom toxicity of potent sea snake venoms (Tan et al, 2015), (ii) the seeming utility of African polyvalent antivenom at neutralizing the venom of a genus of elapid snakes not including in the immunizing mixture (Whiteley et al, 2019), and (iii) the potential for saw-scaled viper antivenom to be used as an alternative treatment for bites by the boomslang (Dispholidus typus) in regions where the appropriate speciesspecific antivenom is unavailable or unaffordable (Ainsworth et al, 2018). The later of these studies demonstrated crossneutralization between distinct snake lineages (e.g., viper and colubrid), and this surprising finding was ultimately informed by venom comparisons indicating that these snakes had converged upon similar toxin compositions.…”
Section: Therapeutic Implications Treating Snake Envenomationmentioning
confidence: 99%
“…Similar ED 50 values were reported for Antivipmyn-Africa, VACSERA and Fav-Afrique antivenoms against the venom of the forest cobra, N. melanoleuca (1778.8-2777.8 μl/mg) (Fig 2B, S1 Table) [5,38,40]. Two of three antivenoms (Antivipmyn-Africa and SAIMR Polyvalent) tested against N. nivea (cape cobra) venom, demonstrated efficacy in preventing venom-induced lethality in mice, although SAIMR Polyvalent was four times more efficacious (2115.2 vs. 529.9 μl/mg, respectively) [5,42] (Fig 2B, S1 Table). The…”
Section: Antivenom Efficacy Against Neurotoxic Elapid Venomsmentioning
confidence: 99%
“…We also detected expression of cysteine-rich secretory proteins (CRISP), snake venom metalloproteinases (SVMP) and kunitz type protease inhibitors (KUN) (Figure 2E and S1G). The relative abundance of these toxin classes matched the venom gland tissue at transcriptome level, and the crude venom composition at protein level (Whiteley et al, 2019) (Figure 2E). Of note, the seven-day differentiation protocol increased overall toxin gene expression but reduced the expression of CRISP (Figure 2D and E).…”
Section: Newly Assembled Transcriptome Reveals High Toxin Expression mentioning
confidence: 65%
“…Organoid cluster 3 consisted of cells co-expressing C-type lectin (CTL) and Waprin-related toxins ( Figure S3E) (Torres et al, 2003;Ogawa et al, 2005). CTLs have not previously been detected in the Aspidelaps lubricus venom proteome and did not form an independent cluster in the tissue dataset (Whiteley et al, 2019). Cluster 5, containing cells exclusively derived from differentiated organoids, was devoid of any known toxin expression.…”
Section: Organoids Display Cellular Heterogeneity In Toxin Expressionmentioning
confidence: 99%
See 1 more Smart Citation